The Role of Women in Advocacy and Community Reform - Asy'ari, Khoirul Hadi; Hayati, Dwi Astuti Wahyu Nur; Sa’diyah, Miftahus (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2019)
In advocacy, women need to be identified so that we can attribute a role to their level. The judgment of the thing is part of his conception, which makes the knowledge of women's reality a priority. When we follow the evolution of women's life long ago to this day, we find that it is doomed.The role of women in advocacy: First and before I go on the subject must understand what is the area of advocacy that we want women to do it? Yes, it is the whole society, because this role can only be achieved if the society is included, whose life revives the nation and dies. When he says: